Implementation of Treasury Single Account and Strengthening of Cash Management in Vietnam - World Bank (Washington, DC, 2014)
Vietnam has made progress to improve oversight and control over cash balances for the state budget. The current arrangement however falls short of a treasury single account (TSA), which has led to inefficiencies in the management of cash balances and higher than necessary borrowing costs. In response to this, the Government of Vietnam has embarked on reforms to adopt a TSA and strengthen overall cash management. This policy note provides a review of progress in implementing a TSA system in Vietnam, the remaining challenges and obstacles, and how to overcome these for further TSA and cash management reforms. It is the product of ongoing discussions between the World Bank and the Ministry of Finance. Part A gives background and motivation; part B provides an overview of the state treasury system in Vietnam; part C reviews the progress in establishing a TSA, including against benchmarks of international good practice, and makes recommendations for priority next steps; and part D concludes with a review of cash management functions.